An NBD tertiary amine is a fluorescent quencher and/or a weak green-light fluorophore in H2S-specific probes. Issue 20 (5th May 2022) - Chen, Ruirui; Ye, Haishun; Fang, Tian; Liu, Shanshan; Yi, Long; Cheng, Longhuai
Abstract : The piperazinyl-based NBD probes can efficiently and selectively react with H2 S, where the NBD tertiary amine moiety can be a fluorescent quencher or a weak fluorophore in different cases. Abstract : The thiolysis of NBD piperazinyl amine (NBD-PZ ) is highly selective for H2 S over GSH and has been widely used for the development of many H2 S fluorescent probes. Whether the NBD amine in H2 S-specific probes could be a fluorescent quencher should be further clarified, because NBD amines have been used as environment-sensitive fluorophores for many years. Here, we compared the properties of NBD-based secondary and tertiary amines under the same conditions. For example, the emission of NBD-N(Et)2 is much smaller in water and less responsive to changes in polarity than that of NBD-NHEt . The emission of NBD-PZ-TPP is also smaller than that of NBD-NH-TPP both in aqueous buffer and in live cells. In addition, confocal bioimaging signals of NBD-PZ-TPP with excitation at 405 nm and 454 nm are much weaker than that at 488 nm. Based on these results as well as the previous work on NBD-based probes, we discuss and summarize the design strategies and sensing mechanisms for different NBD-based H2 S probes. Moreover, NBD-PZ-TPP may be a useful tool for reaction with and imaging of mitochondrial H2 S in live cells. This work should be useful for clarification of the roles of NBD in H2 S-specific fluorescent probes as well as for facilitating the development of future NBD-based probes.